Kant’s method of teaching philosophy - Belas, Lubomir; Zakutna, Sandra (Studia Kantiana, 2016)
The article focuses on Kant’s emphasis on the importance of education, especially teaching philosophizing, in the development of moral character of an individual who is at the same time able to think for oneself. The Enlightenment motto "Sapere aude!" is discussed in the first part of the article as it represents the groundwork for teaching students to philosophize (not philosophy, which is impossible to teach). The ability to think for oneself is an important issue in Kant’s Announcement of the Programme of Lectures for the Winter Semester 1765-1766 in which he explains the zetetic method of teaching and describes his plan of lectures on metaphysics, logic, doctrine of virtues and physical geography - all of them being based on a new way of teaching that plays an important role in shaping and cultivating the character of students. The last part of the article aims to show Kant’s educational method incorporated in his cosmopolitan theory.